Transformasi Minyak Jelantah: Pemberdayaan Perempuan Desa Lewat Inovasi Sabun Ramah Lingkungan di Desa Gempol, Karanganom Kabupaten Klaten - Aprilia Sefi Widayanti; Luthfiah Ramadhani; Intan Nurul Fitriana; Irghi Ahmad Kurniawan; Nurul Fibrianti; Darodji (Pencerah, 2025)
Gempol Village, Karanganom Subdistrict, Klaten Regency, has experienced significant growth in home-based micro, small, and medium enterprises (MSMEs). This development has positively impacted the local community of Gempol Village but has also posed environmental challenges. One negative impact of these home-based MSMEs is the increasing production of used cooking oil (Indonesian: jelantah) or waste cooking oils (WCOs). WCOs that are not properly disposed of can pollute the environment. Significant pollution will happen to the water and soil ecosystem. Hence, to address this issue, innovations in this specific waste management are needed. That can be achieved by involving and empowering local communities to transform the waste into economically valuable products. One potential use of cooking oil waste lies in its fatty acid content, which is an important matter for producing valuable soap bars. Therefore, this work program, which empowers the local communities, was conducted by aiming to increase the value of used cooking oil by processing it into soap. A soap-making training using cooking oil waste has been successfully conducted in Gempol Village, bringing tangible benefits to the community.